Self-Complementary Dimer of Zinc(II) Porphyrins through Coordination with Oxygen Ligands - Ke, Yuanzhen; Wang, Hsian-Wen; Liu, Zhichang; Luh, Tien-Yau (Synthesis, 2023)
Oxygen ligands have been shown to play a critical role in the formation and organization of metalloporphyrin assemblies and natural chlorosomes. In this work, mutually complementary head-to-tail dimers of zinc(II) porphyrins were synthesized through the coordination of zinc with the imide group and 7-oxanorbornene oxygen ligands. UV/Vis absorption and emission, 1H NMR as well as FT-IR analyses were used to determine the structure. The dimerization association constant K has been determined to be 5.6 M–1 and 29 M–1, respectively, by the dilution experiment.
Keywords: metalloporphyrins; self-assemble; aggregation; coordination; oxygen ligands; dimerization